(untitled) (Advances in Civil and Architectural Engineering, 2023)
Magnetorheological dampers (MRDs) are devices that adjust their damping properties in response to an external magnetic field. Large-scale MRDs have been successfully used as vibration control devices in structures. This study focuses on modelling and optimizing an MRD using COMSOL Multiphysics. Various parameters, such as coil turns and current, are optimized to achieve the maximum flux value in the MRD. The simulation yielded a maximum magnetic flux of 0,44 T with 500 coil turns. Based on the optimized MRD parameters, a numerical equation is then used to calculate the total damping force. The maximum numerical and experimental damping forces corresponding to a 2,0 A current were 989,39 and 1004,63 N, respectively. The numerical damping force is then compared to the experimental results to validate the accuracy of the model. The MRD is integrated into a scaled-down reinforced concrete frame and subjected to a cyclic loading test for performance evaluation. The results show that the MR dampers improve the performance of the frame structure, increasing its load-carrying capacity and energy dissipation by 19,45 % and 20,43 %, respectively. The findings of the study provide valuable insights into the behaviour of MRDs and their optimization using numerical simulations, as well as highlight the importance of experimental validation for accurate prediction of the performance of MRDs in practical civil engineering applications.